2019
DOI: 10.1136/bmjopen-2018-028805
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical payments to certified oncology specialists in Japan in 2016: a retrospective observational cross-sectional analysis

Abstract: ObjectiveThis study investigated payments made by pharmaceutical companies to oncology specialists in Japan, what the payments were for and whether the receipt of such payments contravened any conflict of interest (COI) regulations.Design, setting and participantsPayment data to physicians, as reported by all pharmaceutical companies belonging to the Japan Pharmaceutical Manufacturers Association, were retrospectively extracted for 2016. Of the named individual recipients of payments, all certified oncologists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 43 publications
(90 citation statements)
references
References 38 publications
6
84
0
Order By: Relevance
“…Kathyrn et al reported Pharma tended to make more payments to male physicians than to female ones in the US [16,17]. Further, in Japan, similar findings were observed in the case of certified oncologists [13], and our findings were consistent with the previous studies. Although there are 1.25 times more male dermatologists than female dermatologists (3189 male dermatologists and 2543 female dermatologist) in Japan [18], the lower proportion of female CPG authors and lower Pharma payments to female CPG authors could not be explained merely by the discrepancy in numbers alone.…”
Section: Plos Onesupporting
confidence: 91%
See 2 more Smart Citations
“…Kathyrn et al reported Pharma tended to make more payments to male physicians than to female ones in the US [16,17]. Further, in Japan, similar findings were observed in the case of certified oncologists [13], and our findings were consistent with the previous studies. Although there are 1.25 times more male dermatologists than female dermatologists (3189 male dermatologists and 2543 female dermatologist) in Japan [18], the lower proportion of female CPG authors and lower Pharma payments to female CPG authors could not be explained merely by the discrepancy in numbers alone.…”
Section: Plos Onesupporting
confidence: 91%
“…Universities and professors traditionally have been regarded as a symbol of authority in Japan. As repeatedly suggested in our previous works, university professors have a strong influence on practices and treatments in their clinical fields, and other physicians tend to follow a professors' decision of suitable treatment without question or criticism [13]. This result supports the idea that Pharma may be targeting and making payments to senior physicians who can influence of set clinical practice.…”
Section: Plos Onesupporting
confidence: 83%
See 1 more Smart Citation
“…result, their commercial products will generate a greater income and help maximize their profits. 6,[8][9][10] In most countries, pharmaceuticals are officially regulated by governmental authorities, such as the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA). The staff of these regulatory authorities are usually prohibited from having financial dealings of any kind with pharmaceutical companies as a means of avoiding undesirable influence and possible corruption, especially as their roles and positions are quite public.…”
Section: How Might This Change Clinical Pharma-cology or Translationamentioning
confidence: 99%
“…If this is not the case, public trust and faith in medicine and the nation's health system will be further eroded 6,7 . However, previous studies have repeatedly shown that pharmaceutical companies often make payments to highly influential specialists, such as university professors and clinical practice guideline authors, presumably hoping that, as a result, their commercial products will generate a greater income and help maximize their profits 6,8‐10 …”
mentioning
confidence: 99%